Analisis Motivasi Belajar Siswa pada Implementasi Model Pembelajaran Direct Instruction - Lutfiah Nur Hidayati; Restu Utami; Antuni Wiyarsi; Jaslin Ikhsan (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to analyze students’ learning motivation on the implementation of Direct Instruction learning model in Muhammadiyah Pakem Senior High School. The research design used in this research is pre-experimental with a one-shot case study. The study sample consisted of all class X students with a total of 11 students. Sampling technique using is purposive sampling. Data collection techniques were carried out by questionnaires to measure students' learning motivation. The data analysis used is a descriptive analysis by calculating the percentage of the overall score on the learning motivation questionnaire. The results of the study were the level of students’ learning motivation in Muhammadiyah Pakem Senior High School in the high-very high category. The present of the teachers in the Direct Instruction learning model have a big role to develop students' learning motivation